Qualitative Research Methodology and its Scope in Health Services Research - Patel Naiya (Journal of Neurological Research And Therapy, 2020)
Health services research is a multidisciplinary field which involves policy makers, health care providers, as well as quality outcomes professionals of the health services provided in an organizational setting to name some. Using qualitative research methodology to get insights of both the provider and patient experience down the pipeline can help strengthen what is lacking. Bridging the gap of translation research by not just surveys 1 might be an appropriate research methodology, however, inclusion of case studies, ethnographies might help stakeholders in the field, to visualize in depth phenomenon occurring in health services research field. Telly medicine, commercial digital health status trackr might be some of the inetrventions to improvise health care services, however, knowing what are the actual needs at individual level might efficiently help in redistribution of resources or policy laws. Recruiting for clinical trials through story telling communication technology2,3, might help in recruitment for novel drug therapies to explore possibilities, however, exploring the barriers to enroll for the clinical trials, or why the drug might work effectively in some cultural population and why not on others, can only be efficiently explored through qualitative research methodologies.
Keywords: Health services methodologies